1. Producer Gas from Indigenous Solid Fuels 2. Conversion of Oil-Fired Boilers to Utilize Solid Fuels - Cruz, Ibarra E. (Philippine Engineering Journal; Vol 31 No 1 (2010), 2021)
No Abstracts. Foreword by Edwin N. Quiros.